Design and Research of S-Box Based on Dynamic Strategy - Zhouquan Du; Qijian Xu; Jie Zhang; Xudong Zhong; Zhulin An (Dianxin kexue)
Block cipher encryption is the mainstream method of information security application,and it has been widely used in wireless sensor networks.S-box which is one of the core modules of block cipher algorithm has a direct and significant impact on the entire cipher algorithm.In order to improve the secure strength of the block cipher algorithm with the limited resource,a lot researches on it and analyses of S-box structure design had been done,then the design scheme of dynamic S-box which can improve the security of S-layer by learning from the architecture of Feistel and the reconstruction of S-box came out.The result of the test showed that the project really can work on the increasing of security.